Effects of a commercial calcium protein hydrolysate on the salt tolerance of Diospyros kaki L. cv. "Rojo Brillante" grafted on Diospyros lotus L. - Visconti, Fernando; De-Paz, José M.; Bonet, Luis; Jordá, Miguel; Quinones, Ana; Intrigliolo, Diego S. (2017)
Diospyros lotus L. is advantageously used as rootstock for Diospyros kaki L. cv. “Rojo Brillante” in most plantations of Eastern Spain. However, one of the few drawbacks of D. lotus L. as rootstock, is the high sensitivity to soil salinity, and specifically chloride, it imparts to the scion, which is visually detected as an extensive late season leaf necrosis. Several complex mixtures of organic polymers such as calcium protein hydrolysates (CPH) have been recommended to counteract salt stress on plants. Nevertheless, the effects of these commercial complex products on tree crops, are not usually rigorously studied, nor satisfactorily explained. The effects on soil and plant of the addition of a commercial CPH in the irrigation water of a D. kaki L. cv. “Rojo Brillante” plantation grafted on D. lotus L. were studied during two successive seasons. Soil salinity and chloride contents, significantly, but slightly, increased in CPH treated subplots, while at the same time leaf chloride contents decreased. These effects suggest a lower chloride plant uptake in CPH treated subplots. The lower chloride uptake in CPH treated trees was accompanied by less leaf necrosis, and also lower leaf water potential. However, the yields of CPH treated and non-treated trees were statistically non-different. The build-up of compatible solutes, mainly proline and glycine betaine, in addition to the biosynthesis of salt-stress-response proteins, which would have been stimulated by the CPH, could explain the observed effects. However, the likely biosynthesis of all these substances may have drawn plant resources from fruit development, thus explaining why yields were the same in treated and non-treated subplots despite the trees in treated subplots showed better adaptation to soil salinity.